Gambaran Dukungan Sosial dalam Membentuk Resiliensi pada Penyintas Kanker Payudara - Setya Rahayu; Fitrania Maghfiroh (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast cancer is a deadly disease that not only attacks the body but also causes psychological effects such as depression, anxiety, and prolonged stress in patients. In dealing with their illness, subjects receive considerable social support from family, friends, and the community, which helps reduce pressure and build resilience. This study aims to explore more deeply the role of social support in building resilience in breast cancer survivors. This study employs a qualitative approach, utilizing a single case study. The subject is a 37-year-old female breast cancer survivor who works as a freelancer and is also a housewife. The subject has been suffering for 3 years and has shown resilience during her treatment. Data were collected through observation of the subject's behavior and semi-structured interviews based on Edith Gortberg's resilience guidelines. Data analysis was conducted using the Miles and Huberman model with three stages: reduction, presentation, and conclusion. The results of the study showed that the subject experienced initial emotional trauma, such as fear, rejection, and isolation after diagnosis and the loss of a child, exacerbated by repeated surgeries and preoperative anxiety about skin grafts. However, social support from husbands, families, and communities, coupled with individuals' resilient, optimistic, and open-minded internal characteristics, coping skills, and good emotional management, significantly shaped their resilience, helping them rise from their state of despair.